Positive electrode solid energy storage material, preparation method and application of positive electrode solid energy storage material in flow battery

By preparing a positive electrode solid energy storage material composed of active materials, conductive materials, water-based binders and inorganic salts, the problems of low volume energy density and high industrial cost of the liquid flow battery are solved, and high volume capacity density and low cost energy storage effects are achieved.

CN119725655APending Publication Date: 2025-03-28BEIJING HENGCHU RUINENG TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411907731.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The volume energy density of the flow battery is low, resulting in the need of a larger storage tank to store the electrolyte, which takes up a large space. At the same time, the cost of the existing solid energy storage materials is high and the solvent is difficult to handle.

Method used

A positive electrode solid energy storage material prepared by mixing and extruding active materials, conductive materials, water-based binders and inorganic salts is used to prepare solid energy storage materials with a high specific surface area through the water-based binders and inorganic salt pore-making process.

Benefits of technology

It significantly improves the volume capacity of the flow battery, reduces the cost of the overall system, avoids the use of organic solvents, improves the utilization rate of solids, and solves the cost and environmental protection problems in industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725655A_ABST
    Figure CN119725655A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode solid energy storage material, a preparation method and an application of the positive electrode solid energy storage material in a flow battery, and belongs to the technical field of flow batteries. The preparation method specifically comprises the following steps: S1, dissolving a water-based binder in water to obtain a high-molecular polymer solution; s2, mixing the active material, the conductive material and the inorganic salt by adopting a mixing machine; s3, mixing the high-molecular polymer solution obtained in the step S1 and the mixture obtained in the step S2 by adopting a mixing machine; and S4, extruding the mixture obtained in S3 by adopting an extruder, then preparing the mixture into spherical particles by adopting a granulator, and finally drying to obtain the positive electrode solid energy storage material. The solid energy storage material with high reaction activity is prepared by using the green water-based solvent, the solid utilization rate of the solid energy storage material can exceed 80%, and the solid energy storage material can play a role in different ion environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of redox targeted reaction liquid flow batteries, and in particular to a positive electrode solid energy storage material, a preparation method thereof, and an application in liquid flow batteries. Background Art

[0002] Renewable energy generation has attracted much attention in the power industry due to its cleanliness and sustainability, but its inherent discontinuity and instability may have an adverse impact on the power grid when directly connected to the grid. Therefore, equipping energy storage devices has become an effective means to solve this problem. Among the many energy storage technologies, flow batteries are regarded as one of the most promising technologies in the field of large-scale energy storage due to their high safety performance, capacity-power separation, flexible design, strong scalability and fast response speed. However, the volumetric energy density of flow batteries is generally low, which means that larger tanks are required to store enough electrolyte, taking up more space.

[0003] At present, the technology of adding solid energy storage materials to the electrolyte storage tank to increase the single-side volume capacity is regarded as the optimal solution for high volume energy density batteries. However, in the preparation process of the added solid energy storage materials, PVDF adhesive and NMP are used as solvents, which leads to problems such as high cost and difficult solvent treatment in its industrialization project.

[0004] In summary, liquid flow batteries show great potential in the field of renewable energy storage, but their development is limited by key technical problems such as volume capacity. Therefore, the present invention provides a method for preparing a positive electrode solid energy storage material, and the prepared energy storage material is used in a liquid flow battery, which solves the problems of high industrialization cost and green sustainable production while ensuring high battery performance and significantly improving the volume capacity of the liquid flow battery. Summary of the invention

[0005] The purpose of the present invention is to provide a positive electrode solid energy storage material and a preparation method and application in a liquid flow battery to solve the problems in the above-mentioned background technology.

[0006] To achieve the above object, the present invention provides a method for preparing a positive electrode solid energy storage material, wherein the positive electrode solid energy storage material is prepared by mixing and extruding an active material, a conductive material, an aqueous binder, an inorganic salt and water, and specifically comprises the following steps:

[0007] S1, dissolving an aqueous binder in water to obtain a high molecular polymer solution;

[0008] S2, mixing the active material, the conductive material and the inorganic salt using a mixer;

[0009] S3, mixing the high molecular polymer solution obtained in S1 and the mixture obtained in S2 using a mixer;

[0010] S4, extruding the mixture obtained in S3 by an extruder, and then preparing it into spherical particles by a granulator, and finally drying it to obtain a positive electrode solid energy storage material.

[0011] Preferably, the mass proportions of active material, conductive material and aqueous binder in the prepared positive electrode solid energy storage material are 70%-95%, 0%-15% and 5%-20% respectively.

[0012] Preferably, the active material is one or more of Prussian blue, Prussian white, Berlin green, lithium iron phosphate, sodium vanadium phosphate, and metal-doped derivatives of zinc, copper, manganese, and nickel of the active material.

[0013] Preferably, the conductive material is one or more of graphite, carbon black, graphene, and carbon nanotubes.

[0014] Preferably, the water-based binder is one or more of polytetrafluoroethylene, polyacrylamide, sodium polyalginate, polyvinyl alcohol, carboxymethyl cellulose, styrene butadiene rubber, and cellulose acetate.

[0015] Preferably, the inorganic salt is a dissolving inorganic salt or a reactive inorganic salt, and the concentration of the inorganic salt is 2% to supersaturation.

[0016] Preferably, the dissolution-type inorganic salt is one or more of sodium chloride, sodium sulfate, potassium chloride, and potassium sulfate; and the reaction-type inorganic salt is one or more of sodium carbonate, sodium bicarbonate, and calcium hydroxide.

[0017] Preferably, in step S1, the water-based binder is a polymer with a number average molecular weight of 100,000 to 1,000,000; and the mass volume ratio of the water-based binder to water is 1 g: 1 mL to 10 mL.

[0018] The present invention also provides a positive electrode solid energy storage material obtained by the above preparation method, wherein the size of the positive electrode solid energy storage material is 0.5-2.5 mm.

[0019] The present invention also provides the use of the positive electrode solid energy storage material prepared by the above preparation method in a liquid flow battery.

[0020] Therefore, the present invention provides a positive electrode solid energy storage material, a preparation method and an application in a flow battery, which have the following beneficial effects:

[0021] (1) The present invention uses a hydrophilic and positive electrode electrolyte-friendly binder to form uniform hydrophilic and positive electrode electrolyte-friendly sites on the substrate surface, making the material hydrophilic, so that when in contact with the electrolyte, it can participate in the reaction more quickly and completely. In addition, the inorganic salt pore-forming process used to produce a solid energy storage material with an ultra-high specific surface area, and its solid utilization rate exceeds 80%.

[0022] (2) The present invention replaces the binder in the solid energy storage material with an aqueous material, and forms pores through aqueous binders and inorganic salts that are hydrophilic and affinic to the positive electrode electrolyte, thereby achieving a comparable or higher solid utilization rate. The entire system avoids the use of organic solvents, which not only solves the problem of organic solvent recovery, but also reduces the cost of the overall system.

[0023] (3) The various active substances selected in the present invention all have the advantage of low cost. In addition, the good compatibility of neutral aqueous solution with materials significantly reduces the cost of equipment purchase and subsequent maintenance, which leads to reduced investment costs and is conducive to industrialization.

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a cycle performance diagram of the liquid flow battery system prepared in Example 3 of the present invention;

[0026] Figure 2 This is a side view of the rate performance of the liquid flow battery system prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] The invention provides a method for preparing a positive electrode solid energy storage material. The positive electrode solid energy storage material is prepared by mixing an active material, a conductive material, an aqueous binder, an inorganic salt and water in a mixer and extruding the mixture in an extruder.

[0028] The mixer used for mixing in the present invention can be any one of a planetary mixer, an inclined mixer, a three-dimensional swing mixer or a double-helix cone mixer.

[0029] The present invention applies the prepared positive electrode solid energy storage material to the preparation of a high volume capacity density liquid flow battery system, wherein the positive electrode electrolyte storage tank stores a positive electrode electrolyte, and a positive electrode active substance is added thereto, and the positive electrode solid energy storage material prepared above is arranged in the positive electrode electrolyte storage tank, and the negative electrode electrolyte storage tank stores a negative electrode electrolyte, and a negative electrode active substance is added thereto.

[0030] The present invention places the positive electrode active material in a complex positive electrode electrolyte system containing one or two cations. The cation composition in this electrolyte system covers both the cations carried by the positive electrode active material itself and the cations added as supporting electrolytes. Under the premise of ensuring that the standard activity product between the anions and cations of the positive electrode active material remains constant, by increasing the diversity of cation types in the positive electrode electrolyte, the activity product formed by a single cation and an anion of the positive electrode active material is effectively suppressed, and the solid material can be used in one or more cation systems. In order to increase the volume capacity of the positive electrode side, the present invention also provides the above-prepared solid energy storage material in the positive electrode electrolyte storage tank.

[0031] The positive electrode active material is ferrocyanide or ferrocyanide, and the concentration is 0.1 mol / L-1 mol / L; wherein the ferrocyanide is one or more of potassium ferrocyanide, sodium ferrocyanide or ammonium ferrocyanide; and the ferrocyanide is one or more of potassium ferrocyanide, sodium ferrocyanide or ammonium ferrocyanide.

[0032] It should be noted that the battery provided in the embodiment of the present invention can be a symmetrical battery or a full battery. The symmetrical battery is an electrochemical testing device whose positive and negative electrode materials are the same and can be used to perform material performance tests under the condition of eliminating the interference of the negative electrode. The full battery is a complete battery, including the positive and negative electrodes, diaphragm, electrolyte, shell and other parts.

[0033] The supporting electrolyte of the positive electrode electrolyte or the negative electrode electrolyte is one or more of LiCl, Li2SO4, LiNO3, LiOH, KCl, K2SO4, KNO3, KOH, NaCl, Na2SO4, NaNO3, NaOH, NH4Cl, (NH4)2SO4, Bu4NClO4. The types of cations in the positive electrode active material of the supporting electrolyte in the positive electrode electrolyte are 1 to 4. When the types of cations exceed four, the effect of improving the solubility of the positive electrode active material in the positive electrode electrolyte is not obvious. Moreover, the introduction of more than four cations will affect the cycle stability of the positive electrode electrolyte and increase the internal resistance of the battery.

[0034] The aqueous binder used in the present invention plays a very important role in the process of preparing positive electrode solid energy storage material particles. First of all, the interaction between the covalent and non-covalent interactions between the binder and the surface of the active material, including the self-healing properties of hydrogen bonds, is one of the key factors in achieving long-term stable circulation. In addition, the aqueous binder has more functional groups than the commonly used PVDF. In the process of forming stable particles through the self-entanglement of the binder and combining with the surface of the active material, the aqueous binder can provide more support and the particles have better mechanical integrity. And in some high-quality embodiments, the interaction between the alkaline surface groups of the carbon powder and the acidic alginate chains leads to a longer cycle life and a slight increase in resistance during circulation.

[0035] The use of a single binder can change the interface of the active material. But the corresponding binder content is relatively high, reaching 10% or even higher. However, such a high dosage is not suitable for large-scale production. In addition, high viscosity and very low solid content lead to high energy consumption and low effective mass load (i.e., lower energy density) during drying. When the content of the binder is reduced, the modification effect of the "hydrophilic modification layer" on the active material will be affected. After a long period of circulation, the mechanical stress during the circulation process will cause particle degradation. When using a composite binder, first of all, different binders can provide a network structure with stronger mechanical strength inside the particles during the mutual entanglement process, and different binders have different binding sites for the active material when combined with the active material, which can form a stronger layer of chemical structure network. At the same time, different binders form new hydrogen bonds, van der Waals forces, strong electrostatic effects, etc., so that the active material can be protected from destruction when the binder content is low.

[0036] In addition, in the preparation process of energy storage materials with non-electrode contact and non-electrochemical charge and discharge, the present invention focuses on exploring the interaction between special groups of binders and conductive agents and molecules in iron-based aqueous solutions to significantly promote reaction kinetics. Specifically, binders and conductive agents containing specific functional groups are selected, which can form strong interactions with molecules in iron-based aqueous solutions, such as hydrogen bonds, coordination bonds, etc. This interaction not only enhances the structural stability of the material, but also promotes the transmission efficiency of electrons and ions within the material. Furthermore, by finely controlling the composition and concentration of the iron-based aqueous solution, as well as parameters such as temperature and time during the preparation process, the interaction between molecules is optimized, thereby achieving a significant improvement in reaction kinetics.

[0037] At the same time, in order to improve the overall reaction rate, a variety of particle pore-making processes have also been explored. During the particle preparation process, different inorganic salts are added, and the inorganic salts are soaked in water after the particles are dried. Not only can the influence of inorganic salt dissolution on the electrolyte be eliminated, but also suitable pores can be prepared for the particles to increase the contact area with the electrolyte. In some high-quality embodiments, a saturated sodium bicarbonate aqueous solution is used in the granulation process, and dilute hydrochloric acid is used for soaking after the particles are dried. The reaction rate of the particles prepared in this way is 160% of that using the same concentration of sodium chloride. A saturated manganese oxide aqueous solution is used in the granulation process, and dilute hydrochloric acid is used for soaking after the particles are dried. The reaction rate of the particles prepared in this way is 145% of that using the same concentration of sodium chloride.

[0038] The technical solution of the present invention is further described below by means of the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to the present invention and belong to the scope of protection of the present invention.

[0039] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present invention. The word "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present invention, as long as there is no technical contradiction or conflict, the various technical features mentioned in each embodiment can be combined in any way to form a corresponding implementable technical solution.

[0040] Unless otherwise defined, the technical terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs; the use of relevant terms herein is only for describing specific embodiments and is not intended to limit the present invention.

[0041] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.

[0042] The positive active material used in the specific implementation is potassium ferrocyanide, and the specific energy storage material is prepared from Prussian blue (PB), that is, ferric ferrocyanide. Take this as an example to explain the charging and discharging principle of the flow battery. The chemical formula of ferric ferrocyanide is Fe4 Ⅲ [Fe Ⅱ(CN)6]3 is a coordination compound. Prussian blue can form reduced Prussian white (PW). The specific reaction equation for the targeted oxidation and reduction of the positive active material anion to the solid energy storage material is:

[0043]

[0044] During the charging process, an oxidation reaction occurs at the electrode of the positive half-cell. The reaction equation is: [Fe(CN)6] 4- →[Fe(CN)6] 3- +e - , with the oxidation state product [Fe(CN)6] 3- As the concentration gradually increases, the actual potential E of the positive electrolyte in the positive electrolyte storage tank gradually increases and exceeds the potential of Prussian white (PW), and the reverse reaction of equation (1) occurs, so that the oxidized [Fe(CN)6] 3- The reduced Prussian white (PW) is oxidized to the oxidized Prussian blue (PB), and the solid energy storage material stores electrical energy, and [Fe(CN)6] 3- Reduced to [Fe(CN)6] 4- ,[Fe(CN)6] 4- The positive electrode circulation pump enters the positive electrode half-cell and continues to charge. The above process is repeated until all Prussian white (PW) is oxidized to Prussian blue (PB), [Fe(CN)6] 4- All oxidized to [Fe(CN)6] 3- , charging is completed. This process completes the joint energy storage of the positive electrode active material and the solid energy storage material.

[0045] During the discharge process, a reduction reaction occurs at the electrode of the positive half-cell. The reaction equation is: [Fe(CN)6] 3- +e - →[Fe(CN)6] 4- , along with the reduced product [Fe(CN)6] 4- As the concentration gradually increases, the actual potential E of the positive electrolyte in the positive electrolyte storage tank gradually decreases and is lower than the potential of Prussian blue (PB), and a forward reaction occurs in equation (1), and the reduced state [Fe(CN)6] 4- By reducing Prussian blue (PB) to Prussian white (PW), the solid energy storage material releases the stored electrical energy, and [Fe(CN)6] 4- Oxidized to [Fe(CN)6] 3- ,[Fe(CN)6] 3- The positive electrode circulation pump enters the positive electrode half-cell and continues to discharge. The above process is repeated until all Prussian blue PB is reduced to Prussian white (PW), [Fe(CN)6] 3-All reduced to [Fe(CN)6] 4- , the discharge ends. This process completes the joint energy release of the positive electrode active material and the solid energy storage material.

[0046] Example 1

[0047] In this embodiment, the positive electrode active material in the liquid flow battery system is 0.15 mol / L K4Fe(CN)6+0.15 mol / L Na4Fe(CN)6, and the supporting electrolyte is 1 mol / L KCl; the negative electrode active material is 0.3 mol / L K3Fe(CN)6, and the supporting electrolyte is 1 mol / L KCl; 2 g PB solid energy storage material (85% PB, 10% carbon black, 3% PTFE, 2% PAM, saturated sodium bicarbonate solution, 0.1 g sodium bicarbonate) is loaded in the positive electrode storage tank; the diaphragm is a modified Nafion117 diaphragm; the constant current charge and discharge cycle performance test of the liquid flow battery system is carried out, the flow rate of the positive electrode electrolyte and the negative electrode electrolyte are both 30 mL / min, the charging cut-off voltage is 0.5 V, the discharging cut-off voltage is -0.5 V, and the current density is 30 mA / cm 2 The average coulombic efficiency of the liquid flow battery system in this embodiment is 99.9%.

[0048] Example 2

[0049] In this embodiment, the positive electrode active material in the liquid flow battery system is 0.3 mol / L Na4Fe(CN)6, and the rest is the same as in Example 1. The average coulombic efficiency of the liquid flow battery system in this embodiment is 99.9%.

[0050] Example 3

[0051] In this embodiment, the positive electrode active material in the liquid flow battery system uses 0.3 mol / L K4Fe(CN)6, and the rest is the same as in Example 1. The cycle performance diagram is as follows: Figure 1 As shown by Figure 1 It can be seen that the battery of the flow battery system of this embodiment is 12.5mA cm -2 Both the blank sample and the experimental sample have stable cycle performance under the current density, and the average coulomb efficiency is 99.9%. The charge and discharge curve of the flow battery is shown in Figure 2 As shown by Figure 2 It can be seen that the blank sample capacity of the flow battery is 394 mAh. After adding 2gPB, the capacity of the experimental sample increased to 507 mAh, and the capacity increased by 113 mAh.

[0052] Example 4

[0053] In this embodiment, the positive electrode active material in the liquid flow battery system is 0.3 mol / L K4Fe(CN)6+0.3 mol / L Na4Fe(CN)6, and the rest is the same as in Example 1. The average coulombic efficiency of the liquid flow battery system in this embodiment is 99.9%.

[0054] Example 5

[0055] In this embodiment, the positive electrode active material in the liquid flow battery system is 0.4 mol / L K4Fe(CN)6, the negative electrode active material is 0.4 mol / L K3Fe(CN)6, and the rest is the same as in Example 1. The average coulombic efficiency of the liquid flow battery system in this embodiment is 99.9%.

[0056] Example 6

[0057] In this embodiment, except that the positive electrode active material is 0.5 mol / L K3Fe(CN)6, the negative electrode active material is 0.5 mol / L K3Fe(CN)6, and the supporting electrolyte is 1 mol / L NaCl, the rest is the same as Example 1. The average coulombic efficiency of the liquid flow battery system in this embodiment is 99.9%.

[0058] Example 7

[0059] In this embodiment, the positive electrode active material is 0.6 mol / L K4Fe(CN)6, the negative electrode active material is 0.6 mol / L K3Fe(CN)6, the supporting electrolyte is 1 mol / L NaCl, and the rest is the same as in Example 1. The average coulombic efficiency of the flow battery system in this embodiment is 99.9%.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a positive electrode solid energy storage material, characterized in that: The positive electrode solid energy storage material is prepared by mixing and extruding active materials, conductive materials, aqueous binders, inorganic salts and water, and specifically includes the following steps: S1, dissolving an aqueous binder in water to obtain a high molecular polymer solution; S2, mixing the active material, the conductive material and the inorganic salt using a mixer; S3, mixing the high molecular polymer solution obtained in S1 and the mixture obtained in S2 using a mixer; S4, extruding the mixture obtained in S3 by an extruder, and then preparing it into spherical particles by a granulator, and finally drying it to obtain a positive electrode solid energy storage material.

2. The method for preparing a positive electrode solid energy storage material according to claim 1, characterized in that: The mass proportions of active materials, conductive materials and aqueous binders in the prepared positive electrode solid energy storage material are 70%-95%, 0%-15% and 5%-20% respectively.

3. The method for preparing a positive electrode solid energy storage material according to claim 1, characterized in that: The active material is one or more of Prussian blue, Prussian white, Berlin green, lithium iron phosphate, sodium vanadium phosphate, and metal-doped derivatives of zinc, copper, manganese, and nickel of the active material.

4. The method for preparing a positive electrode solid energy storage material according to claim 1, characterized in that: The conductive material is one or more of graphite, carbon black, graphene, and carbon nanotubes.

5. The method for preparing a positive electrode solid energy storage material according to claim 1, characterized in that: The water-based binder is one or more of polytetrafluoroethylene, polyacrylamide, sodium polyalginate, polyvinyl alcohol, carboxymethyl cellulose, styrene butadiene rubber, and cellulose acetate.

6. The method for preparing a positive electrode solid energy storage material according to claim 1, characterized in that: The inorganic salt is a dissolving inorganic salt or a reactive inorganic salt, and the concentration of the inorganic salt is 2% to supersaturation.

7. The method for preparing a positive electrode solid energy storage material according to claim 6, characterized in that: The dissolution-type inorganic salt is one or more of sodium chloride, sodium sulfate, potassium chloride, and potassium sulfate; the reaction-type inorganic salt is one or more of sodium carbonate, sodium bicarbonate, and calcium hydroxide.

8. The method for preparing a positive electrode solid energy storage material according to claim 1, characterized in that: In step S1, the water-based binder is a polymer with a number average molecular weight of 100,000 to 1,000,000; and the mass volume ratio of the water-based binder to water is 1 g: 1 mL to 10 mL.

9. A positive electrode solid energy storage material, characterized in that: The positive electrode solid energy storage material is prepared by the preparation method according to any one of claims 1 to 8, and the size of the positive electrode solid energy storage material is 0.5-2.5 mm.

10. A positive electrode solid energy storage material is used in a liquid flow battery, characterized in that: The positive electrode solid energy storage material is prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Non-aqueous electrolyte secondary battery

    CN105981209A

  • Vanadium redox flow battery based on solid energy storage material and preparation method of vanadium redox flow battery

    CN118645668A

  • Battery monomer and preparation method thereof, battery and electric equipment

    CN118645676A

  • KR20240002009A